Effects of central arterial aging on the structure and function of the peripheral vasculature: implications for end-organ damage - Mitchell, Gary F. (American Physiological Society, 2008)
Over the past decade, numerous studies have shown that increased aortic stiffness is associated with major cardiovascular disease end points, including heart disease, stroke, and kidney disease. Cardiac abnormalities and enhanced atherogenesis in the setting of increased pulsatile load on heart and arteries have been well described. However, recent studies have shown a further association between excessive pressure pulsatility and a number of afflictions of aging that share a predominant microvascular etiology, including many forms of kidney disease and cognitive impairment. In these disorders, microvascular remodeling and impaired regulation of local blood flow, which are related to large artery stiffness and pressure pulsatility, are associated with evidence of diffuse microscopic tissue damage. This brief review will summarize age-related changes in aortic and peripheral vascular function and will discuss potential mechanisms leading from changes in properties of large arteries to excessive pressure pulsatility, abnormal microvascular structure and function, and end-organ dysfunction and damage.